Metode Konseling Dalam Penanganan Kasus Kekerasan Seksual - Ati Kusmawati; Lutfi Inayah; Yuwafi Prilia Ramadhani; Muhammad Kiyanjaya (Lembaga Pengembangan Kinerja Dosen, 2023)
There are increasing cases of sexual violence involving underage teenagers and even children who are victims of these heinous acts. In this case, guidance and counseling can help victims of sexual violence because the purpose of guidance and counseling is to show, guide or direct other people to a better/right path. In writing this research, the author used literature study techniques systematically so that the steps taken could be carried out more easily. Trauma can affect anyone who experiences extraordinary events, such as war, rape, death due to violence against loved ones, and natural disasters such as earthquakes and tsunamis. The traumatic counseling process does not have any fundamental differences from the counseling process in general, including the basic skills that must be understood and applied properly. Implementation of CBT counseling to overcome trauma in victims of sexual violence can be done by following the CBT counseling framework guidelines. Implementation of CBT counseling to overcome trauma in victims of sexual violence can be done by following the CBT counseling framework guidelines.